Turbulent eddies in boundary layers on smooth and rough flat plate - Chowdhury, Shamsuzzaman, author; Fluid Mechanics Program, College of Engineering, Colorado State University, publisher (Colorado State University. Libraries, 1966)
This study represents one in a series of boundary layer investigations which are undertaken in order to obtain a definition of the roughness characteristics of a surface from the turbulence structure in the boundary layer near the surface. It is attempted to discuss the effect of the roughness in the structure of the turbulent eddies found near the boundary by comparing space correlations and spectra which were measured in the boundary layer on smooth and rough flat plates. The experimental investigations were made with a flat plate placed at a height of 2.0 ft. from the floor of a wind tunnel which had a 6 ft. x 6 ft. cross- section. The size of the plate used was 6 ft. x 3 ft. To obtain a rough surface condition, gravel which passed through a #7 sieve and are retained on a #8 sieve was glued to the surface of the aluminum plate. The density of the roughness material was 120 particles per square inch. Mean velocity profiles were measured on six stations with ambient air velocity of 30 fps at a condition of zero pressure gradient which were obtained by constructing a false ceiling to the wind tunnel roof. The measurements were analyzed in terms of the "wall law" and the "velocity-defect law" for smooth walls, and agreement with the work of other investigators was found. The logarithmic part of the velocity distribution curve for the rough boundary is shifted parallel to the smooth curve by an amount ∆u/u*=12. The turbulence signals were recorded on magnetic tape. They were obtained by using two single hot-wires, one of which was fixed in position and embedded in the plate surface and the other was mounted on a probe actuator whose position was varied freely in x, y and z directions with respect to the fixed probe. From these data, the turbulent intensities, turbulent spectra, total space correlations and filtered space correlations were determined electronically. Comparison of the results for smooth boundary with those for the rough boundary shows that the smooth surface eddy retains the correlation coefficients for a longer time than that of the rough surface case. The parameter to define the roughness characteristic in the velocity field from the measurement of space correlations was expressed in terms of Lxs/Lxr where Lxs and Lxr is the mean eddy size for smooth and rough boundary respectively.
CER65SC-EJP57.
March 1966.
U.S. Army Material Command Washington 25, D.C.
Keywords: Boundary layer; Turbulence